Oxide-Matrix Based Nanocomposite Materials for Advanced Magnetic and Optical Functionalities - Pellicer, Eva; Rossinyol, Emma; Cabo, Moisés; López-Ortega, Alberto; Estrader, Marta; Suriñach, Santiago; Baró, Maria Dolors; Nogués, Josep; Sort, Jordi (IntechOpen, 2011)
None